(untitled) (mathematica didactica, 2022)
The Corona pandemic presented those involved in education with unprecedented challenges. This can be seen, for example, in the need to conduct distance learning, which in some cases lasted several months and was initially conducted almost without the use of supporting digital teaching formats. So far, it remains unclear how cognitively rich the teachers made their subject lessons under such conditions. The presented exploratory study, based on questions regarding central criteria for assessing the quality of distance learning, investigates this complex of questions for the subject of mathematics by examining the cognitive characteristics and range of variation of the tasks used during the Corona pandemic (N=457) by eight lower secondary mathematics teachers. The findings indicate that mathematics teaching can in part be regarded as very low in activation. This result is supported by the fact that the range of activities demanded in the solution process can be assessed as narrow and that within this range, low cognitive demands are anchored in each case. From the per-spective of a temporal development, this profile is rather stable and at best shows selective developments. These findings are not related in this study to the results from classroom teaching by the same teachers.